Effectivity of Ethanol Extract of Bintaro Seed (Cerbera manghas) as Larvacide against Anopheles aconitus Larvae - Muhammad Natsir; Bambang Sukilarso Sakiman; Yusuf Ari Mashuri (Nexus Kedokteran Translasional, 2016)
Introduction: Malaria is still one of the public health problem that can cause death, especially in the high risk groups; babies, toddlers, and pregnant women. One of the strategy to reduce the number of cases is vector management and control using larvacides which are derived from plants. Bintaro seed (Cerbera manghas) is known containing cerberins, saponins, tanins, and steroids. This study aimed to determine effectivity bintaro seed (Cerbera manghas) ethanol extract as a larvacide against Anopheles aconitus larvae. Methods: This was a laboratory experimental research with post test only control group design. The object of this research was the larva of Anopheles aconitus that was divided into seven groups with each group contains 25 larvae. The research was replicated four times. The negative control group was 100 ml of aquadest. The other six groups contained different concentration of ethanol extract of bintaro seed. They were 0,125%, 0,25%, 0,375%, 0,5%, 0,625%, and 0,75%. The samples then were observered after being stored in 24 hours and the number of dead larvae were counted. The data were analyzed using Probit Regression and Curve Estimation. Results: LC50 and LC99 were 0,118% and 0,728% respectively. The Curve Estimation showed that ethanol extract of bintaro seed affects the mortality of Anopheles aconitus larvae with tight correlation R2 = 0,709. Its linear regression equation was Y = 0,592 + 0,641 X. Conclusions: The ethanol extract of bintaro seed (Cerbera manghas) is effective as a larvacide against Anopheles aconitus larvae with its LC50 in 0,118% and LC99 0,728%. Keywords: bintaro seed (Cerbera manghas), Anopheles aconitus larvae